SEMIOTICS ANALYSIS OF THE QURAN TEXT ABOUT JIHᾹD FĪ SABĪLILLAH IN JULIA KRISTEVA'S SEMANALISYS TO INTERTEXTUALITY APPROACH - Nursidik, Ihsan (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
The interpretation of the Qur'an, especially the word jihād fī sabīlillāh, is often trapped in a standard interpretation legitimized by closed interpretations. The secure interpretations make the meaning of the word lose its original purpose. This specific interpretation makes the meaning of the word jihād fī sabīlillāh lose its original meaning. This article aims to find a methodological review that might be able to open the veil that closes the interpretation of ijtihad in the original meaning of the jihād fī sabīlillāh pronunciation. Julia Kristeva, as one of the thinkers of poststructuralism, introduced the semanalist concept known for its revolutionary interpretation methodology. This research is a type of qualitative research with the analytical-descriptive method. This study will explain the concepts of Kristeva's interpretation of a text and then applied to the interpretation of the pronunciation of Jihad. The study results conclude that the interpretation of Jihad as war is an institutional meaning. In contrast, the hidden meaning of the pronunciation of Jihad, such as 'sincerity', does not get attention and tends to be neglected.